ANALISIS WACANA KRITIS TERHADAP BERITA POLITIK DI MEDIA ONLINE - niswa niswa nisrina (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
In the current digital era, almost overall human activities are very close to online media. Did not rule out the possibility of the Election Contestation or the 2024 Presidential Election will be very close to online media. In this research. Researchers try to conduct an analysis related to the news that has been uploaded by Kompas.com online media using the critical discourse analysis technique Norman Fairclough model. The analysis was carried out because the researcher wanted to see whether in the news that had been uploaded during the period before the election until the election was completed, there was a separate agenda or in this case as a medium of reporting, Kompas.com had a connection with certain pairs. In this study, researchers will use descriptive qualitative research methods with the acquisition of data through the IMA application from PT. Indonesia Indicator. This study also used the theory of critical discourse analysis to see how the Kompas.com reporting process during the 2024 Presidential Election event took place.